Three-dimensional transesophageal echocardiographic assessment of valvar and ventricular aspects in simple and complex mitral valve prolapse. (4th February 2022) - Capotosto, L; Tanzilli, G; Iannucci, G; Viceconte, N; Placanica, G; Mancone, M; Mangieri, E; Miraldi, F; Vitarelli, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose. In mitral valve prolapse (MVP), preoperative assessment of repairability depends primarily on the complexity of the prolapse and is one of the most challenging roles of the echocardiologist. The aim of this study was to investigate whether three-dimensional transesophageal echocardiography helps in the evaluation of both valvar/annular and ventricular aspects in simple (single segment) and complex (multisegmental) MVP. Methods. We studied 24 patients with mitral regurgitation due to MVP using three-dimensional transesophageal echocardiography. Mitral valve (MV), left atrium (LA) and left ventricle (LV) were analyzed. Leaflets surface area, mitral annulus antero-posterior and inter-commissural diameters, area and circumference were determined. Mitral annular disjunction (MAD) defined as a separation between LA-MV junction and LV attachment was evaluated. Papillary muscle to annulus plane distances and inter-papillary distance were obtained. LV global longitudinal and circumferential strain was assessed by speckle tracking echocardiography. Results. Thirteen patients had complex MVP and 11 had simple MVP. Prolapse volume was 6.37 ± 4.68 mL in complex MVP and 1.59 ± 1.21 mL in simple MVP (p = 0.004). Prolapse height was 10.1 ± 2.9 mm in complex MVP and 5.8 ± 3.2 mm in simple MVP (p = 0.003). Volume/height ratio was 0.58 ± 0.29 in complex MVP and 0.21 ± 0.14 in simple MVP (p = 0.001). LV longitudinal strain had a negative correlation with change in prolapse height (r = 0.58, p < 0.001), whereas LV circumferential strain correlated with change in prolapse volume (r = 0.53, p < 0.005). Annular area was 1037 ± 191mm2 in simple MVP and 1842 ± 336mm2 in complex MVP (p < 0.01). MAD was evident in 8 complex MVP patients (61%) and 2 simple MVP patients (18%, p < 0.05). The 3D extension of MAD was significantly related to total (r = 0.54; p = 0.002) and anterior leaflet surface area (r = 0.52; p = 0.004), length from papillary muscles to coaptation (r = 0.61; p = 0.002) and regurgitant orifice (r = 0.66; p < 0.001). Conclusions. In MVP patients 3DTEE helps to refine the characterization of simple and complex prolapse by a combined assessment of leaflets/annular details and ventricular attachment.